The Effectiveness of Guided Inquiry Learning Model to Improve Students' Critical Thinking Skills on Acid-Base Materials - Siti Rohmah; Emmawaty Sofya; Tasviri Efkar; Bayu Saputra (Universitas Lampung, 2020)
This research was aimed to describe the effectiveness of guided inquiry learning model in improving students' critical thinking skills on acid-base material. The population in this study were students of class XI MIA SMA Negeri 3 Metro of the 2019/2020 school year with a sample of class XI MIA 2 as the experimental class and XI MIA 3 as the cotrol class. This research method is a quasi-experimental with pretest postest control group design. The effectiveness of guided inquiry learning modelThis research was analyzed using the two mean difference test at n-Gain and the effect size test on students' critical thinking skills between experimental class that applied guided inquiry learning model and control class. The results showed that guided inquiry learning model had a